Q: What is (7y - 3)(2y - 1)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7y-8 = 6y+1 7y-6y = 1+8 y = 9

10x-7y=-110x+1=7y-2x -10x-1=-25-12x-1=-25-12x=-24x=-24/-12x=210(2)-7y=-120-7y=-121=7y21/7=yy=3

if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7

1 + 7y = 5x - 2 7y = 5x - 3 - 5x = - 7y - 3 x = 7/5y + 3/5 ---------------------

-6

Related questions

7y-8 = 6y+1 7y-6y = 1+8 y = 9

10x-7y=-110x+1=7y-2x -10x-1=-25-12x-1=-25-12x=-24x=-24/-12x=210(2)-7y=-120-7y=-121=7y21/7=yy=3

x+7y=16 ---------------------------1 3x- 7y=4 ---------------------------2 ------------------------------------------------------------------------------------------------------------------ 1+2 x+7y=16 3x-7y=4 4x=20 x=5 substitute x = 5 in x+7y=16 (5)+7y=16 7y=11 y=11/7

So Hey, Step 1: 7y=7y :) Step 2: 7y/7y=49^8 :) Step 3: 49^8/ = *6r1 :) So Hey Again so like you saw all the steps right?? Ok, GOOD :)............................................................................................................................................................................................................. So the reciprocal of 7y is 6^1 :)

if: 2x + 6 = -6 then: 2x = -12 x = -6 if: 5x + 7y = 1 then: 5(-6) + 7y = 1 7y = 31 y = 31/7

x + 7y = 7 ⇒ 7y = -x + 7 ⇒ y = -x/7 + 1 ⇒ y intercept is 1.

1 + 7y = 5x - 2 7y = 5x - 3 - 5x = - 7y - 3 x = 7/5y + 3/5 ---------------------

39

-6

This would be easier with operational signs. If that's + 7y + 4, the answer is (3y + 4)(y + 1). If that's - 7y + 4, it's (1 - y)(4 - 3y)

The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)

39 - 7y = 18,-7y = 18 - 39-7y = -21-7y/-7 = -21/-7y = 3